Association of Static Posturography With Severity of White Matter Hyperintensities - Liu, Bin; Zhao, Guifeng; Jin, Ling; Shi, Jingping (Frontiers in Neurology, 2021)
Background: Impaired gait and balance are associated with severity of leukoaraiosis. Evaluation of balance is based on neurological examination using Romberg's test with bipedal standing, assessment scale, and posturographic parameters. The goal of this study was to determine the relationship between static equilibrium and grades of white matter hyperintensities (WMHs) using static posturography as a quantitative technical method. Method: One hundred and eighteen (118) patients with lacunar infarct were recruited and assessed on MRI with Fazekas's grading scale into four groups. On admission, age, gender, height, weight, Berg Balance Scale (BBS), mini-mental state examination (MMSE), and static posturography parameters were recorded, and their correlations with WMHs were determined. Results: Age was significantly and positively correlated with severity of WMHs (r = 0.39, p < 0.05). WMH score was negatively correlated with BBS score (r = −0.65, p < 0.05) and MMSE score (r = −0.79, p < 0.05). There was a significant positive correlation between track length anteroposterior (AP, with eyes closed) and severity of WMHs (r = 0.70, p < 0.05). Partial correlation analysis and multiple logistic regression analysis indicated that track length AP with eyes closed, was a predictor for the severity of WMHs (p< 0.05). Conclusion: The severity of WHMs is associated with age, cognitive decline, and impairment in balance. Posturography parameter in track length in AP direction with eyes closed in relation to cognition and balance, may be a potential marker for disease progression in WMHs.